Comprehensive Review on Distribution, Socio-Economic Impact and its Management of Striga Hermonthica (Del.) Bent in Ethiopia (Indian Journal of Advanced Botany (IJAB), 2026)
(Striga hermonthica (Del.) Benth.) is one of the world's most adversely affecting weeds of the family Orobanchaceae, which is a major global biotic threat to agriculture in sub-Saharan Africa, including Ethiopia. This review paper examines the prevalence, Socioeconomic impacts, and management options of Striga hermonthica (Del.) Benth. in Ethiopia. Generally to review about this paper various comprehensive literature search was conducted across different areas to come up the general conclusion these are Google Scholar, Web of Science, DOAJ and Science to be the review paper is relevant currently recent work is mandatory based on this idea the year of Studies of published article range between 2016 and 2025 were selected based on relevance and accuracy, quality and their findings were made into thematic areas of covering the prevalence, socioeconomic impact and its management Strategies of Striga hermontica bent in Ethiopia. Many management strategies have been developed to control this weed, including the use of resistant/tolerant varieties, sowing clean seeds free of Striga contamination, rotating cereal hosts with trap crops that induce abortive germination of Striga seeds, intercropping, and applying organic and inorganic soil amendments. This review recommended research on farmer participation, and the government of Ethiopia should conduct regular oversight to assess the prevalence and socioeconomic impacts of this species, implement appropriate protection measures, and prevent further introduction and spread of the striga species into areas not yet infested.